Basic hand splinting a pattern designing approach - Kiel, Judith Hunt (Boston Toronto : Little Brown and Company, 1983)
"This book is for students, as well as for therapist who have not pursued hand rehabilitation but have an occasional need for a basic splinting references, that this book has been written. In addition to a clear explanation of the principles of splinting theory, a detailed explanation of how to make a pattern for a splint is also presented."
Includes index.
English text.